PERAN GREEN TRUST DALAM MEMEDIASI PENGARUH GREEN PERCEIVED VALUE DAN GREEN PERCEIVED QUALITY TERHADAP GREEN PURCHASE BEHAVIOR - Arif afendi (Universitas Ahmad Dahlan, 2019)
The purpose of this research is to analyze the impact of green perceived value and green perceived quality to the green trust, and green perceived value, green perceived quality and green trust to the green purchase behavior. This research was a quantitative and used structural equation model (SEM). The data in this research was primary data with 100 respondents asÂ a sample who used Philips LED lighting in Semarang. The sampling techniques was non probability sampling. The result of the research shows that : There were positive and significant effect of green perceived value and green perceived quality to green trust. Green trust has positive and significant effect to green green purchase behavior. Another result shows green perceived value and green perceived quality have positive and significant effect to green purchase behavior